2020
DOI: 10.9734/afsj/2020/v17i130181
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Composition and Microbiological Evaluation of Vended Street Foods in Parts of Lagos State, Nigeria

Abstract: The presence of microbiological pathogens and proximate composition of vended street foods (VSF) in parts of Lagos State were investigated. The experiment was conducted along 3 local government areas of Lagos State (Marina, Apapa and Yaba) using two factorial design. Eight VSF products investigated were roasted (plantain, fish, yam, corn), suya, meat pie, egg roll and doughnuts, purchased from parts of Lagos State. The result for proximate analysis of VSF sourced from Marina, Yaba and Apapa showed that moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
2
3
Order By: Relevance
“…The determination of the percentage moisture content showed that puff-puff had the highest moisture content of 20.30 among the snack foods examined, while meat-pie had the least (5.40). The percentage moisture content for puff-puff is within the 15.40 and 26.60 previously reported by Israel and Samuel [31] and Pikuda and Ileleboye [32], respectively. The moisture content of meat-pie in this present study is less than the 8.18% reported by Adeyeye and Ayoola [33].…”
Section: Prevalence Of S Aureus In Ready-to-eat Food With Respect To ...supporting
confidence: 86%
See 3 more Smart Citations
“…The determination of the percentage moisture content showed that puff-puff had the highest moisture content of 20.30 among the snack foods examined, while meat-pie had the least (5.40). The percentage moisture content for puff-puff is within the 15.40 and 26.60 previously reported by Israel and Samuel [31] and Pikuda and Ileleboye [32], respectively. The moisture content of meat-pie in this present study is less than the 8.18% reported by Adeyeye and Ayoola [33].…”
Section: Prevalence Of S Aureus In Ready-to-eat Food With Respect To ...supporting
confidence: 86%
“…The percentage carbohydrate content was highest in meat-pie (70.73%) and lowest in puffpuff (4.10%). The value for meat-pie in this study is higher than 55.39 and 60.53% reported by Eke and Elechi [40] and Israel and Samuel [31], respectively. The carbohydrate content of puffpuff (4.10%) is lower than the 65.14% previously reported by Pikuda and Ileleboye [32].…”
Section: Prevalence Of S Aureus In Ready-to-eat Food With Respect To ...contrasting
confidence: 81%
See 2 more Smart Citations
“…Amadi et al [22] have studied the nutritional composition of traditional dishes such as Kekefiyai, Kiri-igina, and Opuru-fulou of Bayelsa State, Nigeria. Israel and Samuel (2020) [23] have studied the proximate composition in eight street foods such as roasted plantain, fish, yam, corn and dough nuts, suya, eggroll, meat-pie from parts of Lagos Nigeria. Similarly, Calubaquib and Suyu [24] have also examined the proximate contents of six fortified Filipino snacks.…”
Section: Discussionmentioning
confidence: 99%